2021
DOI: 10.1111/cen.14599
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot testing of a conversation aid to support the evaluation of patients with thyroid nodules

Abstract: Objective To support patient‐centred care and the collaboration of patients and clinicians, we developed and pilot tested a conversation aid for patients with thyroid nodules. Design, Patient and Measurements We developed a web‐based Thyroid NOdule Conversation aid (TNOC) following a human‐centred design. A proof of concept observational pre–post study was conducted (TNOC vs. usual care [UC]) to assess the impact of TNOC on the quality of conversations. Data sources included recordings of clinical visits, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…AI is just a tool to help the physician communicate with patients. A previous study demonstrated that decreased decisional conflict and fewer nodule FNAB are possible with web-based thyroid nodule conversation aid [30]. FNAB should also account for anxiety, life expectancy, comorbidities of the patient, and other relevant considerations.…”
Section: Discussionmentioning
confidence: 99%
“…AI is just a tool to help the physician communicate with patients. A previous study demonstrated that decreased decisional conflict and fewer nodule FNAB are possible with web-based thyroid nodule conversation aid [30]. FNAB should also account for anxiety, life expectancy, comorbidities of the patient, and other relevant considerations.…”
Section: Discussionmentioning
confidence: 99%
“…It includes referrals and test results, recording the course of patients' disease, imaging tests such as X-rays, CT scans, etc., cardiograms, and financial data such as any payments from the user to the medical staff. The EMR serves several different purposes [ 1 , 2 ]. These purposes include a) practically, it is the primary means of communication for the users involved, i.e., the health professionals, paramedics, and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians should also be encouraged to be transparent about nonclinical factors that may influence decision-making (eg, local practice patterns, personal biases, availability of active surveillance). Thyroid nodule conversation aids and information provision have been associated with increased involvement of patients in the decision-making process, clinician satisfaction, decreased decisional conflict, and fewer thyroid biopsies . Finally, educational efforts at both the institutional and national/societal level may help disseminate data on the significance of patient values and preferences in thyroid cancer treatment.…”
mentioning
confidence: 99%